Advances in neurophilosophy - Heinzelmann, Nora (Bloomsbury Academic, 2025)
Bringing together recent case studies and insights into current developments, this collection introduces philosophers to a range of experimental methods from neuroscience. Chapters provide a comprehensive survey of the discipline, covering neuroimaging such as EEG and MRI, causal interventions like brain stimulation, advanced statistical methods, and approaches drawing on research into the development of human individuals and humankind. A team of experts combine clear explanations of complex methods with reports of cutting-edge research, advancing our understanding of how these tools can be applied to further philosophical inquiries into agency, emotions, enhancement, perception, personhood and more. With contributions organised by neuroscientific method, this volume provides an accessible overview for students and scholars coming to neurophilosophy for the first time, presenting a range of topics from responsibility to metacognition
Keywords: Aufsatzsammlung; Neurophilosophie; Psychologie; Philosophy of Mind